High plant diversity alleviates the negative effects of nitrogen deposition on soil nitrogen cycling multifunctionality - Li, Zhuo; Liu, Xiaowei; Zhang, Minghui; Zhang, Bin; Zhang, Tao; Wagg, Cameron; Xing, Fu (Frontiers in Microbiology, 2025)
IntroductionChanges in plant diversity and increased atmospheric nitrogen deposition independently influence soil nitrogen cycling in terrestrial ecosystems. However, the interactive effects of plant diversity and nitrogen deposition on soil nitrogen cycling multifunctionality (NCMF) in grassland ecosystems remain poorly understood.MethodsWe conducted a fully factorial microcosm experiment to quantify the responses and underlying mechanism of soil NCMF to nitrogen addition (0, 5, and 10 g N m−2 yr.−1) and plant diversity gradients (1, 3, and 6 species).ResultsOur results revealed a significant interactive effect between plant diversity and nitrogen addition on soil NCMF. Specifically, high plant diversity alleviated the negative effects of nitrogen addition on soil NCMF. The addition of nitrogen reduced the soil pH, which imposed microbial stress by limiting carbon availability. In contrast, higher plant diversity increased soil organic matter via below-ground carbon inputs, thereby reducing the soil carbon limitation of microorganims and enhancing the soil NCMF.DiscussionOverall, our findings suggest that maintaining or enhancing plant diversity in grasslands could be a key strategy to mitigate the adverse effects of atmospheric nitrogen deposition on soil nitrogen cycling, highlighting the crucial role of plant diversity in regulating ecosystem nutrient cycling under global change.